Rational Design, Structure–Activity Relationship, and Immunogenicity of Hypoallergenic Pru p 3 Variants. Issue 18 (26th June 2019) - Eichhorn, Stephanie; Hörschläger, Angelika; Steiner, Markus; Laimer, Josef; Jensen, Bettina M; Versteeg, Serge A; Pablos, Isabel; Briza, Peter; Jongejan, Laurian; Rigby, Neil; Asturias, Juan A; Portolés, Antonio; et al.
Abstract : Scope: Allergies to lipid transfer proteins involve severe adverse reactions; thus, effective and sustainable therapies are desired. Previous attempts disrupting disulfide bonds failed to maintain immunogenicity; thus, the aim is to design novel hypoallergenic Pru p 3 variants and evaluate the applicability for treatment of peach allergy. Methods and results: Pru p 3 proline variant (PV) designed using in silico mutagenesis, cysteine variant (CV), and wild‐type Pru p 3 (WT) are purified from Escherichia coli . Variants display homogenous and stable protein conformations with an altered secondary structure in circular dichroism. PV shows enhanced long‐term storage capacities compared to CV similar to the highly stable WT. Using sera of 33 peach allergic patients, IgE‐binding activity is reduced by 97% (PV) and 71% (CV) compared to WT. Both molecules show strong hypoallergenicity in Pru p 3 ImmunoCAP cross‐inhibition and histamine release assays. Immunogenicity of PV is demonstrated with a phosphate‐based adjuvant formulation in a mouse model. Conclusions: An in silico approach is used to generate a PV without targeting disulfide bonds, T cell epitopes, or previously reported IgE epitopes of Pru p 3. PV is strongly hypoallergenic while structurally stable and immunogenic, thus representing a promising candidate for peach allergen immunotherapy. Abstract : Engineering of the lipid transfer protein Pru p 3 from peach results in the generation of stable protein fold variants. These molecules demonstrate very low allergenic potency opposed to the wild‐type allergen. Proline variant presents enhanced integrity and elicits an immune response in a mouse model, thus representing a candidate molecule for allergen immunotherapy of peach allergic patients.